Nonalcoholic fatty liver disease associated with metabolic syndrome: Influence of liver fibrosis stages on characteristics of very low-density lipoproteins - Lucero, Diego Martín (2017)
Background We evaluated possible changes in VLDLcharacteristics, and metabolic related factors, in MetS-associated NAFLD and accompanying liver fibrosis. Methods We studied 36 MetS patients with biopsy-proven NAFLD (MetS + NAFLD) and 24 MetS without ultrasound NAFLD evidence. Further, MetS + NAFLD was sub-divided according to fibrosis stage into, non-to-moderate (F0–F2, n = 27) and severe (F3–F4, n = 9) fibrosis. We measured: lipid profile, VLDL composition and size (size exclusion-HPLC), CETP and lipoprotein lipase (LPL) activities and adiponectin. Additionally, in MetS + NAFLD type IV collagen 7S domain was measured. Results MetS + NAFLD showed increased VLDL-mass, VLDL particle number, VLDL-triglyceride% and large VLDL-% (p < 0.04). CETP activity tended to increase in MetS + NAFLD (p = 0.058), while LPL activity was unchanged. Moreover, in MetS + NAFLD, adiponectin was decreased (p < 0.001), and negatively correlated with VLDL-mass and VLDL particle number (p < 0.05), independently of insulin-resistance. Within MetS + NAFLD group, despite greater insulin-resistance, patients with severe fibrosis showed lower plasma triglycerides, VLDL-mass, VLDL-triglyceride%, large VLDL-% and CETP activity (p < 0.05), while type IV collagen was increased (p = 0.009) and inversely correlated with large VLDL-% (p = 0.045). Conclusions In MetS, NAFLD is associated with larger and triglyceride over-enriched circulating VLDLs, of greater atherogenicity. However, when NAFLD progresses to severe fibrosis, circulating VLDL features apparently improved, probably due to early alterations in hepatic synthetic function.